2016
DOI: 10.1007/s12350-015-0240-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after inappropriate nuclear myocardial perfusion imaging: A meta-analysis

Abstract: Background The relationship between inappropriate MPI and cardiovascular outcomes is poorly understood. We sought to systematically review the literature on appropriate use criteria (AUC) for MPI, including temporal trend of inappropriate testing and resulting cardiovascular outcomes. Methods We searched the MEDLINE database for studies related to AUC and MPI. The co-primary outcomes were abnormal test results and the presence of cardiac ischemia. Random effects odds ratios (OR) were constructed using DerSim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…This is one of a series of reports from this group on the utility of appropriate use criteria in guiding optimal referral patterns to stress myocardial perfusion imaging. [3][4][5][6][7] In this report, the authors report that there was poor concordance between appropriate use criteria developed by the ACC as compared to the ACR, with a kappa statistic of 0.32-supporting modest agreement between the two statements. As there is no definitive ''gold standard'' for appropriate indications, this finding of modest concordance is reason for caution and pause as to whether variability in practice patterns will be observed.…”
mentioning
confidence: 77%
“…This is one of a series of reports from this group on the utility of appropriate use criteria in guiding optimal referral patterns to stress myocardial perfusion imaging. [3][4][5][6][7] In this report, the authors report that there was poor concordance between appropriate use criteria developed by the ACC as compared to the ACR, with a kappa statistic of 0.32-supporting modest agreement between the two statements. As there is no definitive ''gold standard'' for appropriate indications, this finding of modest concordance is reason for caution and pause as to whether variability in practice patterns will be observed.…”
mentioning
confidence: 77%
“…25 A significant body of literature demonstrated that appropriate MPI use enhances its acumen in risk stratification, reduces radiation risk, and improves its clinical value. [27][28][29][30][31][32][33] Physicians are faced with multiple, occasionally discordant, AUC from different organizations. For example, there is substantial discordance between the multimodality AUC for the detection and risk assessment of stable ischemic heart disease developed by the American College of Cardiology, ASNC, and several other societies and the Appropriateness Criteria set forth by the American College of Radiology (ACR).…”
Section: Appropriate Use Reportingmentioning
confidence: 99%
“…In particular, the authors were interested in whether the inappropriate use of MPI resulted in different detection rates of cardiac ischemia or other abnormal findings compared to MPI used according to AUC. 1 It is common in clinical research for an important research topic to have more than one study exploring that topic. There are many reasons for this, from replication and validation to assessing an effect or association in a different population.…”
Section: See Related Article Pp 680-689mentioning
confidence: 99%